2019
DOI: 10.1111/tpj.14174
|View full text |Cite
|
Sign up to set email alerts
|

Mg‐dechelatase is involved in the formation of photosystem II but not in chlorophyll degradation in Chlamydomonas reinhardtii

Abstract: Summary The STAY‐GREEN (SGR) gene encodes Mg‐dechelatase which catalyzes the conversion of chlorophyll (Chl) a to pheophytin (Pheo) a. This reaction is the first and most important regulatory step in the Chl degradation pathway. Conversely, Pheo a is an indispensable molecule in photosystem (PS) II, suggesting the involvement of SGR in the formation of PSII. To investigate the physiological functions of SGR, we isolated Chlamydomonas sgr mutants by screening an insertion‐mutant library. The sgr mutants had red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 49 publications
2
12
0
Order By: Relevance
“…Chl breakdown in senescent leaves begins with the magnesium dechelation of Chl a and the production of Phein a by SGR1/2. Phein a is dephytylated to Pheide a by PPH/CLD1 and further degraded to phyllobilins via the PAO/phyllobilin pathway (Kr€ autler and H€ ortensteiner, 2014;Chen et al, 2019). In green leaves, Chlide a can be further degraded by the PAO/phyllobilin pathway via conversion to Pheide a by SGRL (Chen et al, 2019).…”
Section: Clh1 and Clh2 Are Highly Expressed In Young Leavesmentioning
confidence: 99%
See 1 more Smart Citation
“…Chl breakdown in senescent leaves begins with the magnesium dechelation of Chl a and the production of Phein a by SGR1/2. Phein a is dephytylated to Pheide a by PPH/CLD1 and further degraded to phyllobilins via the PAO/phyllobilin pathway (Kr€ autler and H€ ortensteiner, 2014;Chen et al, 2019). In green leaves, Chlide a can be further degraded by the PAO/phyllobilin pathway via conversion to Pheide a by SGRL (Chen et al, 2019).…”
Section: Clh1 and Clh2 Are Highly Expressed In Young Leavesmentioning
confidence: 99%
“…Phein a is dephytylated to Pheide a by PPH/CLD1 and further degraded to phyllobilins via the PAO/phyllobilin pathway (Kr€ autler and H€ ortensteiner, 2014;Chen et al, 2019). In green leaves, Chlide a can be further degraded by the PAO/phyllobilin pathway via conversion to Pheide a by SGRL (Chen et al, 2019). Chl, chlorophyll; Chlide, chlorophyllide; Phein, pheophytin; Pheide, pheophorbide; pFCC, primary fluorescent Chl catabolite; NCCs, non-fluorescent Chl catabolites; CLH, chlorophyllase; CLD1, Chl dephytylase 1; CHLG, Chl synthase; CAO, Chlide a oxygenase; NYC1, non-yellow coloring 1 (Chl b reductase); HCAR, 7-hydroxymethyl Chl a reductase; PPH, pheophytinase; SGR, STAY-GREEN (Chl a Mgdechelatase); SGRL, STAY-GREEN-LIKE (Chlide/Chl a Mg-dechelatase); PAO, pheophorbide a oxygenase.…”
Section: Clh1 and Clh2 Are Highly Expressed In Young Leavesmentioning
confidence: 99%
“…Remarkably, Phein a was an essential molecule in photosystem (PS) II, so SGRs might affect the formation of PSII. Despite the SGRs in Arabidopsis and Chlamydomonas reinhardtii having the same catalytic property, the physiological functions of SGRs were diverse (Chen et al 2018 ). For example, SGRs in Arabidopsis took part in Chl degradation while SGRs in Chlamydomonas reinhardtii participated in PSII formation (Chen et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the SGRs in Arabidopsis and Chlamydomonas reinhardtii having the same catalytic property, the physiological functions of SGRs were diverse (Chen et al 2018 ). For example, SGRs in Arabidopsis took part in Chl degradation while SGRs in Chlamydomonas reinhardtii participated in PSII formation (Chen et al 2018 ). Although the recent studies have demonstrated that SGRs are able to remove Mg from Chl a to initiate its breakdown, little is known about the domain basis of its functionality.…”
Section: Introductionmentioning
confidence: 99%
“…Total protein extracts and thylakoids were isolated as described in (Ramundo et al, 2013). Blue native polyacrylamide gel electrophoresis (BN-PAGE) was performed according to (Chen et al, 2019; Wittig et al, 2006). The resolving gel of BN-PAGE used was 4.1-14% T (w/v), while the stacking gel was 3.6% T (w/v), where T stands for the total concentration of acrylamide and bisacrylamide monomers.…”
Section: Methodsmentioning
confidence: 99%